Exploring usability principles for educational online courses: a case study on an open platform for online education - Kateryna V. Vlasenko; Sergii V. Volkov; Iryna V. Lovianova; Irina V. Sitak; Olena O. Chumak; Nataliia H. Bohdanova (Academy of Cognitive and Natural Sciences, 2023)
This article delves into the crucial issue of effectively implementing usability principles in educational internet resources. By engaging with the latest research in the field, we investigate the influential factors shaping the outcomes of online education. Through a comprehensive analysis, we identify and examine six well-established criteria of usability design: Information Quality, System Navigation, System Learnability, Visual Design, Instructional Assessment, and System Interactivity. Additionally, we propose the existence of a seventh criterion termed Responsiveness. To shed light on the practical application of usability principles, we focus on the open platform "Higher School Mathematics Teacher" as a case study. Through a survey administered to 203 respondents, comprising both teachers and students, we sought to gather their valuable perspectives as the initial users of the platform. The insights gained from this study provide guidance for the implementation of usability criteria on the platform, particularly during the development of online courses. The findings strongly suggest that all seven subcategories of usability are pivotal in the design of online courses on the platform. This research contributes to the ongoing discourse on usability implementation in educational technology, offering valuable insights for developers, educators, and researchers alike. By recognizing the significance of these criteria, educational internet resources can be enhanced to create more engaging, accessible, and effective learning environments.